Study of toxin production of microcystis under laboratory condition with different nutrient treatment - Lee, Li Keat (Universiti Malaysia Sarawak (UNIMAS), 2015)
Aquaculture is an important industries in Malaysia, however, cyanobacterial blooms with potential toxins are problematic in pond water management in aquaculture. In this study, potential toxin-producing cyanobacteria, Microcystis sp. were isolated from selected aquaculture ponds in Indigenous Fisheries Production and Research Center, Tarat, Sarawak. The isolated Microcystis sp. were successfully maintained and mass culture using BG11 medium under laboratory condition. In-situ and ex-situ water parameter of selected aquaculture pond were recorded and microcystins concentration were detected in bloom-forming ponds using HPLC analysis. There are no significant relation found between chl-a concentration and microcystins concentration of pond samples and culture samples. Meanwhile, in nutrient experiment using different N:P (nitrogen:phosphorus) ratio, NP15(15:1 ratio) give the best growth performance of Microcystis sp. with highest optical density and overall specific growth rate. Highest microcystins concentration was detected in sample with N:P ratio 15:1 at 8.510 μg mg-1. In this experiment, a relation between microcystins production and growth of Microcystis in term of growth density and growth rate was observed but no relation was observed between nitrate concentration and microcystins production. Nevertheless, N:P ratio = 15 was found to be the optimum nutrient ratio for growth of Microcystis sp. and highest microcystins content was detected.